Contributions from citizen science to science education: an examination of a biodiversity citizen science project with schools in Central Europe. Issue 17 (22nd November 2018) - Kelemen-Finan, Julia; Scheuch, Martin; Winter, Silvia
ABSTRACT: Despite the rising popularity of Citizen Science (CS) projects, there is little empirical evidence for effects on learning outcomes, particularly when young people are involved. It is also often not clear how CS projects are linked to science education (SE) research. The aim of this study was to examine biodiversity CS projects in an outdoor school class context and to measure the effects on individual learning outcomes (ILOs) with a perspective for SE. Five learning outcomes considered important for CS were tested: interest, self-efficacy/mastery, motivation, behaviour and attitude. These ILOs were measured via eight different scales and tested in an evaluation study of a large CS project with 428 students aged 8–18. Students recorded hedgehogs, wild bee activity, birds and butterflies in gardens. Results showed that students' interest and motivation, as well as perceived mastery increased during the project. Most remarkably, positive attitudes towards wild animals, natural gardens and biodiversity rose significantly. For most ILOs there were significant differences between age groups: Primary school students showed the highest ILOs and also provided most database entries. The authors describe how well biodiversity CS projects contribute to SE aims and how discrepancies between educational and scientific aims in CS projects may be addressed.